Assessment of Heavy Metal (Zinc, Copper, Lead and Cadmium) Contamination in Common Edible Shellfish Species of the Hooghly River and Sunderbans, India - Chakrabarti, Kausiki; (Paul), Sobhana Palit (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The content of four heavy metals (Zinc, Copper, Lead and Cadmium) in muscles of three shell fish species - prawns -Penaeus monodon and Penaeus indicus and crabs-Scylla serrata, the most prime shellfish food resources of human in the domestic and international market were studied at four stations in the estuarine belt near Bay-of-Bengal which receives wastes of various types from industries and various anthropogenic activities. The samples were digested by acid digestion. The metal contents were quantified using an AAS (Atomic absorption spectrophotometer). The distribution of trace metals accumulated in the muscle tissues of the above mentioned species was in the order- Zn > Cu> Pb> Cd. In the present study, levels of Zinc in the shell fishes ranged from 07.44±0.65 to 128.10 ±2.96 ; Cu ranged from 5 ±0.15 to 99.14 ±1.31; Pb varied from 1.67± 0.14 to 23.99 ± 0.79 and Cd ranged from 1.29± 0.35 to 7.09 ± 0.80.The concentration of the four metals exhibited spatial variation as station 1 >station 2 > station 3 > station 4, which could be a reflection of different bioavailability of metal concentrations in the water body at different stations. The results obtained showed that the metal concentrations in most of the cases were above the threshold value recommended by WHO. Metals such as Cu, Zn, Pb, Cd, can affect various aquatic organisms as well as human being either directly or indirectly as they can enter into the food chain and may be biomagnified at higher trophic levels which is one of the top concerns for human health. Essential heavy metals such as Zinc and Copper are relatively less harmful at low concentration while non-essential metals such as Cd and Pb are highly toxic even at low concentrations.